CONSTRUCTIVISM THROUGH PROJECT-BASED LEARNING MODEL ON NATURAL SCIENCE LEARNING SUBJECTS IN ELEMENTARY SCHOOLS (LITERATURE REVIEW) - Rahadian; Erry Utomo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper describes the theory of constructivism as an effort to increase students' understanding of Natural Science learning subjects in elementary schools using Project-Based learning in learning practices. PjBL is based on constructivism theory, which prioritizes the urgency of the knowledge-compiling process by students themselves actively, based on the knowledge that has been previously possessed. PjBL is a learning process that supports student-centered learning and experiential learning. PjBL can be one of the solutions for teachers in an attempt to direct students to understand the material, foster creativity, work on projects, and strengthen the process of collaborative group cooperation. Natural Science learning subject in elementary schools aims to provide direct experience to students in order to gain a more meaningful understanding and insight about the environment, which becomes a medium for students to learn about themselves and their environment. The research in this paper is qualitative and uses literature review methods. Journal search comes from the search at Google Scholar, Researchgate, ERIC, and others. The data analysis techniques are (1) data reduction, which means that to remove various things that are not needed and focusing on the important ones, (2) data exposure, which is describing data presented based on certain sub- sections, and (3) drawing conclusions from the results of recent research that has not conducted yet before.